The Influence of Inquiry Lesson Learning on Students' Scientific Reasoning Ability in Ecosystem Material - Ajijah, Melani; Juhanda, Aa; Setiono, Setiono (BIOEDUSCIENCE, 2023)
Background: This study aims to determine the influence of applying the Inquiry Lesson learning model on the scientific reasoning abilities of Grade X students. Method: This type of research uses a quasi-experiment. The sample for this research was A total of 55 students in the science program grade 10 at one of the Madrasah Aliyah Public Schools (MAN) were involved. The instrument used is in the form of scientific reasoning ability test questions in the form of reasoned multiple-choice questions of 15 questions. The research design used is the Non-equivalent Control Group. The second instrument uses a student response questionnaire to learning using the inquiry lesson learning model, which consists of 12 questions. Results: The average N-Gain score was 0.48 in the moderate category, and the scientific reasoning abilities of students in the control class produced an average pretest score of 56.12 and a post-test average score of 70.13 with an average score of 70.13. N-Gain score of 0.32. The hypothesis test obtained a significance value of sig (2-tailed) 0.004, then H0 was rejected, and H1 was accepted. The emergence of scientific reasoning abilities of experimental class students on each indicator varies but generally has an N-Gain score in the moderate category. Student response questionnaires regarding the inquiry lesson learning model showed an average score in the excellent class (61-80). Conclusion: the conclusion in this study is that there is an increase in inquiry lesson learning on students' scientific reasoning abilities in Grade X ecosystem material.